Safety, Affect and Families. Challenges in the Reintegration Process of Demobilized Combatants of Armed Groups in Santander, Colombia - Vargas-Parra, Jakeline; Diáz-Pérez, Ángela María; Anctil-Avoine, Priscyll (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
In Colombia, the process of reintegration into civilian life is intended to support the legal life projects of people who have belonged to organized illegal armed groups. This process has been led by the Agencia para la Reincorporación y la Normalización (national agency for reintegration into civilian life) through the Ruta de Reintegración (reintegration plan) since 2011. Drawing froma collaborative research project, the objective of this article is to analyze, from a gender perspective, the obstacles experienced by people in the process of reintegration, especially regardingsafety, family and community relations, as well as affect and subjectivity. Qualitiativemethodology was used and it was divided in two actions: (1) review of the scientific literature on gender and reintegration and; (2) 24 semi-structured interviews conducted with people in the reintegration process and their life partners in the department of Santander. The analysis of the proposed categories allowed us to identify three elements to improve the support offered to people in the process of reintegration: the implementation of a gender perspective, the integration of the family in the whole process of reintegration and, finally, the sensitizationof the host community.